The Famous Five (Five Go Down to The Sea) - Blyton, Enid; Eileen, A. Soper (Great Britain Hodder and Stoughton, 1997)
Julian, Dick, Anne, George and Timmy the dog find excitement and adventure wherever they go in Enid Blyton's most popular series.